Effects of ingesting a commercial thermogenic product on hemodynamic function and energy expenditure at rest in males and females - Wilborn, C.; Taylor, L.; Poole, C.; Bushey, B.; Williams, L.; Foster, C.; Campbell, B. (Applied Physiology, Nutrition, and Metabolism, 2009)
The purpose of this study was to examine the effects of a commercially available thermogenic product (TP) on resting energy expenditure (REE) and hemodynamic variables in a randomized, double-blind, placebo (PL)-controlled study. Eight male (age: 23.0 ± 3.70 years, weight: 95.77 ± 16.44 kg, height: 182.4 ± 7.87 cm) and 10 female (age: 23.6 ± 4.81 years, weight: 67.25 ± 5.74 kg, height: 172.42 ± 10.31 cm) physically active individuals participated in this study. Participants reported to the laboratory on a 10-h fast and performed baseline testing on REE, heart rate, and blood pressure. Participants were then randomly assigned to ingest 3 capsules of either an experimental TP or a vitamin E PL. Criterion variables were then measured at 1-, 2-, and 3-h post ingestion. Data were analyzed by 2-factor analysis of variance (ANOVA) using SPSS, version 16.0 (SPSS Inc., Chicago, Ill.). Supplementation of the TP resulted in a significant main effect for time (p = 0.040) and for interaction (p < 0.01) in REE when compared with PL. Post hoc analysis revealed that there was no significant difference (p > 0.05) between groups at baseline, but the TP group was significantly higher (p < 0.01) than the PL group at 1-, 2-, and 3-h post, with peak values being achieved at 2-h post time point. The TP group also experienced an overall increase in REE by 17.3%, 19.6%, and 15.3% at the 1-, 2-, and 3-h time points, respectively, over baseline values. Conversely, the PL group experienced a reduction in REE by 2.5%, 1.8%, and 0.3% at the same time points compared with baseline values. There was no significant change in heart rate, systolic blood pressure, or diastolic blood pressure in either group. Taken on a daily basis, a TP may increase overall energy expenditure. Caloric expenditure significantly increased at all 3 time points in the TP group, whereas the PL group experienced no change in energy expenditure.